Isoterm Adsorpsi Arang Kulit Jengkol Sebagai Adsorben CO2 - Muhammad Fadhil Rahman; Adjar Pratoto; Dendi Adi Saputra; Akio Kodama (Jurnal Teknik Mesin, 2023)
The concentration of carbon dioxide (CO2) gas in the atmosphere continues to increase every year, mainly due to human activities such as burning fossil fuels for energy, industrial processes, and transportation. The development of CO2 gas reduction research continues to be carried out, one of which is the adsorption process using adsorbents. The research was carried out by looking at the effect of variations in activating agent and activation temperature on adsorbents as CO2 adsorbers and how N2 and pore size distribution influence CO2 adsorption. The active carbon adsorbent used comes from jengkol peel which is carbonized via the pyrolysis method. Adsorbents are made by varying the type of activating material (KOH, Urea, and KOH+urea) and activation temperature (600℃, 700℃, and 800℃). The active ingredient KOH+urea has better absorption capacity than other variations, but not too high. N2 gas does not really affect the CO2 adsorption process because it has a low N2 adsorption isotherm, so it is not worrying if the CO2 adsorption process also contains N2 in the air. Based on measurements with Belsorp-Max II, the data obtained is only specific surface area data, this is due to the small surface pores of the adsorbent. The temperature of 800℃ has a better specific surface area than other variations, this is also by the higher CO2 adsorption capacity. So it is concluded that the pore surface area influences the ability to absorb CO2. Based on the data obtained, jengkol peel charcoal is not suitable as a CO2 adsorbent because it has a low pore surface area and adsorption isotherm